Determinan Keputusan Pembelian Helm Di Kota Surabaya: Harga, Citra Merek, Gaya Hidup, Dan Kualitas Produk - Rafida Febriana Widya Putri; Didit Darmawan (Jurnal of Management and Social Sciences, 2023)
This study aims to investigate the effect of price, brand image, lifestyle, andproduct quality on purchasing decisions for Cargloss helmets. The research method uses a quantitative approach with a questionnaire survey of 100 consumer respondents who buy Cargloss helmets. The results show that price, brand image, lifestyle, and product quality have a positive and significant effect on purchasing decisions. Overall, these factors simultaneously also have a positive and significant influence. Companies are advised to set competitive prices with market research to maintain the attractiveness of Cargloss. To build brand identity, companies can emphasise the speciality of Cargloss helmets in design, innovation and other added values. Promotion is also needed to associate Cargloss helmets with consumers' lifestyles. The company management should invest in quality control, quality raw materials, and adoption of latest technology in the production process.